2009
DOI: 10.1093/geronb/gbn035
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults Respond Quickly to Angry Faces Despite Labeling Difficulty

Abstract: Two experiments examined young-old differences in speed of identifying emotion faces and labeling of emotion expressions. In Experiment 1, participants were presented arrays of 9 faces in which all faces were identical (neutral expression) or 1 was different (angry, sad, or happy). Both young and older adults were faster identifying faces as "different" when a discrepant face expressed anger than when it expressed sadness or happiness, and this was true whether the faces were schematics or photographs of real … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
29
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 39 publications
7
29
2
Order By: Relevance
“…This is consistent with studies showing that both young and older adults rapidly and automatically detect emotional information in a visual search task, regardless of valence (Leclerc & Kensinger, 2008), as well as evidence that young and older adults demonstrate equivalent levels of spontaneous mimicry of happy and angry subliminal faces (Bailey & Henry, 2009). The data align more specifically with studies showing that older adults do not differ from young in implicit threat detection (Mather & Knight, 2006;Ruffman et al, 2009), and are capable of processing positive information when voluntary control is limited (Allard & Isaacowitz, 2008;Bannerman et al, 2011). Taken together, the evolutionary drive that promotes automatic avoidance of threat and approach of reward (see Davis & Whalen, 2001) appears to persist into older adulthood.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with studies showing that both young and older adults rapidly and automatically detect emotional information in a visual search task, regardless of valence (Leclerc & Kensinger, 2008), as well as evidence that young and older adults demonstrate equivalent levels of spontaneous mimicry of happy and angry subliminal faces (Bailey & Henry, 2009). The data align more specifically with studies showing that older adults do not differ from young in implicit threat detection (Mather & Knight, 2006;Ruffman et al, 2009), and are capable of processing positive information when voluntary control is limited (Allard & Isaacowitz, 2008;Bannerman et al, 2011). Taken together, the evolutionary drive that promotes automatic avoidance of threat and approach of reward (see Davis & Whalen, 2001) appears to persist into older adulthood.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, recall that older adults are as proficient as young in tasks assessing early, and therefore relatively automatic responding to threatening faces (Mather & Knight, 2006;Ruffman et al, 2009), including when presented subliminally (Bailey & Henry, 2009). There is further evidence for the biological significance of approaching reward (Davis & Whalen, 2001), suggesting that older adults' attention might also be subconsciously cued by positive expressions, such as happiness.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, few studies have found increased emotional response to negative stimuli in older adults. In particular, older adults demonstrated deficits in experiencing and recognizing angry facial emotions (Ruffman et al, 2009;Vanyukov et al, 2014), but there may be qualitative differences hidden by static face recognition. Thus, it seems important to test whether older adults would have difficulties recognizing angry faces using a more dynamic paradigm.…”
mentioning
confidence: 99%
“…On the other hand, in a recent study (Ruffman, Ng, & Jenkin, 2009), both young and older adults were faster distinguishing schematic and photographic faces as "different" when a discrepant face expressed anger than when it expressed sadness or happiness. Similarly, affective priming and the automatic attentional bias during detection of threatening facial expressions (Hahn, Carlson, Singer, & Gronlund, 2006;LaBar et al, 2005) have been reported to be no different between older adults and younger adults.…”
Section: Introductionmentioning
confidence: 73%